IMPLEMENTASI KEBIJAKAN TENTANG PENGANGKATAN PEGAWAI NEGERI SIPIL DALAM JABATAN FUNGSIONAL MELALUI PENYESUAIAN/INPASSING DI LINGKUNGAN PEMERINTAH KABUPATEN BARITO SELATAN - siti mahpuzah; Muslih Amberi; M Riduansyah Syafari (Jurnal PubBis, 2022)
The inpassing policy in functional positions is one of the instruments of various government efforts to create professional civil servants. The research method used in this research is descriptive with a qualitative approach. Data were collected through interviews, documentation and observation with the research subjects were give an policy implementers and civil servants who received the impact of the policy. The results of the study illustration that the implementation of the inpassing policy for functional positions has been running even though it has not shown any significant progress and the inpassing organizational structure has had a positive impact. Supporting Factors of the implementation of policies regarding the appointment of civil servants to functional positions through adjustments/inpassing are the extended implementation time of inpassing, government policies that require certain jobs to be carried out only by functional officials and the support of the South Barito Regency RPJMD while the inhibiting factors for the implementation of this policy are relatively minimal socialization, the process of appointment in a functional position which takes a long time and the requirements are not easy and the understanding of functional positions is minimal.The results of the research imply that the adjustment policy will provide optimal results when the socialization of the policy is also carried out optimally in addition to the goodwill of the government, both the central government and regional governments in implementing the policy in an integrated manner from the center to the regions. Keywords : Implementation, Adjustment